Age, protoliths and tectonic implications of the Toudaoqiao blueschist, Inner Mongolia, China. (1st June 2015) - Miao, Laicheng; Zhang, Fochin; Jiao, Shujuan
Highlights: Magnesioriebeckite characterizes the Toudaoqiao blueschist in northern Great Xing'an Range. Blueschist protoliths are basalts that originated from OIB- and MORB-like mantle sources. The protoliths have formation and metamorphic ages of ca 516 Ma and ca 436 Ma, respectively. The P–T conditions of high-pressure metamorphism are estimated at ∼7 kbar and 450–480 °C, respectively. The blueschist belt marks the suture between the Erguna and Xing'an terranes. Abstract: The Toudaoqiao blueschist is located in the northern Great Xing'an Range of China, part of the eastern Central Asian Orogenic Belt, and was discovered in the 1980s, but the age of its formation and metamorphism and the nature of its protolith, have long remained uncertain. Thin-section examination and microprobe analyses show that the Toudaoqiao blueschist has a mineral assemblage of sodic amphibole + chlorite + epidote + albite + phengite ± apatite ± quartz. Electron microprobe analyses attest that sodic amphibole is magnesioriebeckite in composition. The blueschist-facies metamorphism occurred under metamorphic P–T conditions of ∼7 kbar and 450–480 °C, estimated from pseudosection as well as the compositions of the Na-amphibole and phengite. The protolith of the blueschist is mainly composed of alkali basalt, with a minor amount of tholeiitic basalt. The alkali basalt shows similarities in chemical composition to oceanic island basalt (OIB), suggesting derivation from an OIB-like asthenospheric mantle source in a within-plate setting. The tholeiitic basalt has geochemical features transitional between mid-ocean ridge basalt and island arc tholeiite, which implies an origin from a depleted mantle source that would have been selectively metasomatized in a supra-subduction setting. Sensitive high resolution ion microprobe (SHRIMP) zircon dating confirms that the protolith of the Toudaoqiao blueschist formed at 516 ± 11 Ma, in the middle Cambrian, and experienced blueschist facies metamorphism during the Silurian at ca. 436 Ma. The juxtaposition of the two distinct rock types and the association of the blueschist with mélange suggest that the origin of the Toudaoqiao blueschist belt involve collision–accretionary processes. Based on these new results and regional data, we propose that the Toudaoqiao blueschist belt represents the suture zone between the Erguna and Xing'an terranes and that suturing took place during the Early Silurian period. The southwestern extension of the suture in Mongolia is represented by the Middle Gebi suture.